2018
DOI: 10.1002/jso.25232
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for prediction of postoperative complications in open partial laryngeal surgery

Abstract: Background and Objectives Postoperative morbidity after open partial laryngeal surgery (OPLS) may be serious, leading to a prolonged length of hospital stay and increasing costs. We sought to define the predictive factors of complications and to develop nomograms for patients eligible for OPLS based on clinical and surgical data. Methods We critically reviewed 535 patients with laryngeal carcinoma who underwent OPLS at our Institution from 1982 to 2007. We have identified patients affected by postoperative loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In fact, as demonstrated by Benito et al using a prediction model, the increased age (>70 years) together with the widening of the intervention and resection of one arytenoid correlates with a greater probability of severe impairment of swallowing function, thus causing severe aspiration (25). Gallo et al recently reported similar results when applying a prediction nomogram for dysphagia to 535 patients (26). Simple clinical parameters, coupled with the intermediate degree of hemodynamic stress associated with OLOPS, allow the best candidates to be identified for this procedure: the ability to climb two flights of stairs (= 4 METs) (27) as well a Karnofsky index cut-off placed at a level >80, the latter corresponding to normal activity with effort (28).…”
Section: Selection Of Patientsmentioning
confidence: 63%
“…In fact, as demonstrated by Benito et al using a prediction model, the increased age (>70 years) together with the widening of the intervention and resection of one arytenoid correlates with a greater probability of severe impairment of swallowing function, thus causing severe aspiration (25). Gallo et al recently reported similar results when applying a prediction nomogram for dysphagia to 535 patients (26). Simple clinical parameters, coupled with the intermediate degree of hemodynamic stress associated with OLOPS, allow the best candidates to be identified for this procedure: the ability to climb two flights of stairs (= 4 METs) (27) as well a Karnofsky index cut-off placed at a level >80, the latter corresponding to normal activity with effort (28).…”
Section: Selection Of Patientsmentioning
confidence: 63%
“…Ineffective ligation of the superior laryngeal artery and its branches; (2) Preserved thyroid cartilage wing cover the thyroid cartilage stump, therefore preserved abundant small mucosal capillaries may rebleed due to postoperative hypertension caused by stress responses to pain; (3) Preservation of thyroid cartilage formed of a cavity in the throat, which is unable to provide compression hemostasis on the open cervical tissue; (4) Coughing caused by TOT placement. Once hemorrhage occurs, patients may be required urgent surgical intervention, including reopening of the wounds and hemostatic exploration [3,10]. Furthermore, blood owing into the lower respiratory tract may lead to coughing and even respiratory tract obstruction, meanwhile the accidental swallowing of imperceptible amounts of extravasated blood may result in nausea and vomiting [11].…”
Section: Discussionmentioning
confidence: 99%
“…Vertical partial laryngectomy (VPL) is the most common type of open laryngectomy in our hospital, aiming to preserve a functional larynx [2]. Postoperative hemorrhage is a relatively rare but potentially life threatening and unpredictable complication in patients undergoing VPL, usually occurring within 24 hours of operation [3]. Flow of incisional blood into the lower respiratory tract may cause serious coughing.…”
Section: Introductionmentioning
confidence: 99%
“…9 Complication rate of OPLS is not negligible even in experienced hands so that a careful discussion with the patient regarding benefits and drawbacks is mandatory. 10 In this study, we would like to present the oncological and surgical outcomes in a large series of patients treated with OPLS at our Institution and to report specific clinical and pathological prognostic factors.…”
Section: Introductionmentioning
confidence: 99%